The importance of recording scientific research processes (2016)
Many scientists of the XVII century kept the results of their investigations secret in order to avoid others claiming them as their own. Thought leaders of the time, including Sir Isaac Newton, refrained from announcing many of their discoveries in fear of third parties claiming authorship on said findings.